Gender differences in metabolism; nutrition and supplements - Tarnopolsky, M. A. (Journal of Science and Medicine in Sport, 2000)
For many decades researchers did not consider that there were any differences between the genders in the metabolic response to exercise. As a result, nutritional recommendations and exercise training prescriptions have not considered the potential for gender specific responses. More recently, we and others have demonstrated that females oxidize proportionately more lipid and less carbohydrate during endurance exercise as compared to males. The oxidation of amino acids is similarly lower in females as compared to males during exercise.These gender differences are partially mediated by a higher estrogen concentration in females. Specific areas where there are gender differences in nutritional/supplement recommendations include carbohydrate (CHO) nutrition, protein requirements and creatine (CRM) supplementation. We have shown that females do not carbohydrate load in response to an increase in dietary carbohydrate when expressed as a percentage of total energy intake (i.e., 55-75%), however if they consume >8 g CHOxkg(-1)xd(-1), they show similar increases as compared to males. Top sport male and female athletes require somewhat more dietary protein as compared to sedentary persons. The maximal increase is approximately 100% for elite male athletes and approximately 50-60% for elite female athletes. Fortunately, most athletes habitually consume this level of protein intake. We have recently demonstrated that females show a lesser increase in lean body mass following acute CRM loading as compared to males. Females also did not show reductions in protein breakdown in response to CRM loading, whereas males did. In the future I expect that there will be further research from which gender specific nutritional/supplement recommendations can be made.